An Interplay Between Autophagy and Immunometabolism for Host Defense Against Mycobacterial Infection - Paik, Seungwha; Jo, Eun-Kyeong (Frontiers in Immunology, 2020)
Autophagy, an intracellular catabolic pathway featuring lysosomal degradation, is a central component of the host immune defense against various infections including Mycobacterium tuberculosis (Mtb), the pathogen that causes tuberculosis. Mtb can evade the autophagic defense and drive immunometabolic remodeling of host phagocytes. Co-regulation of the autophagic and metabolic pathways may play a pivotal role in shaping the innate immune defense and inflammation during Mtb infection. Two principal metabolic sensors, AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) kinase, function together to control the autophagy and immunometabolism that coordinate the anti-mycobacterial immune defense. Here, we discuss our current understanding of the interplay between autophagy and immunometabolism in terms of combating intracellular Mtb, and how AMPK-mTOR signaling regulates antibacterial autophagy in terms of Mtb infection. We describe several autophagy-targeting agents that promote host antimicrobial defenses by regulating the AMPK-mTOR axis. A better understanding of the crosstalk between immunometabolism and autophagy, both of which are involved in host defense, is crucial for the development of innovative targeted therapies for tuberculosis.